Biosecutiy Assessment in Some Egyptian Broiler Farms in Relation to The Prevalence of Colibacillosis and Salmonellosis - Botros, Merit B.; Badawy, Basma M.; Elsayed, Mona M.; El-Gohary, Fatma A. (Journal of Advanced Veterinary Research, 2023)
Â The implementation of biosecurity practices in broiler farms is a must for its success. This study was carried out to score the biosecurity measures in three broiler farms in the Dakahliya â€“ Egypt in relation to the seasonal prevalence of colibacillosis and salmonellosis. A cross-sectional study was conducted on randomly selected three broiler farms of different housing systems from (July 2022- June 2023). A total of 540 litter samples were collected during four successive seasons. The computed average score for the three broiler farms; A, B, & C was 14, 15 and 26, respectively, out of 39 estimated items. The findings showed that farm C had better levels of commitment and discipline to biosecurity measures than the other two broiler farms. Highly significant increases of E. coli (p<0.0001) in summer compared to other seasons in the broiler farms with the lowest prevalence rate in farm C with the highest biosecurity score. The same pattern was found for Salmonella prevalence of (p<0.0001) in broiler farms during summer months. Insufficient biosecurity measures in broiler houses were not enough to prevent the entrance and multiplication of E. coli & Salmonella spp. Disciplines, commitment, and regulations of biosecurity need to be enforced in broiler houses to prevent the introduction and spread of diseases.